Characteristics of Goat Farmers in the Implementation of Good Farming Practices (GFP) in Dryland Areas - Veronika Yuneriati Beyleto; Maria Selfiana Pasi; Nila Puspita Sari (ANIMAL PRODUCTION, 2026)
This study aimed to examine the characteristics of goat farmers in the implementation of Good Farming Practices (GFP) in dryland areas. The study was conducted in the Biboki Anleu, North Bikomi, and North Insana sub-districts of North Central Timor Regency, East Nusa Tenggara Province, from June to August 2024. Data were collected from 318 goat farmers with at least two years of farming experience. The study locations were selected through purposive sampling based on accessibility, the highest goat population, and proximity to the border area. The survey method involved direct field interviews and observations of goat husbandry practices. Data were analyzed using descriptive statistics and frequency distributions. The results showed that the average age of the farmers was 47.74 years, and their primary occupation was farming. The majority were male, had completed only elementary school, and had received minimal training or extension services; their average farming experience was 9.69 years. The average herd size was 9.90 goats. However, the adoption of GFP among the farmers was notably low. In conclusion, the study indicated that the characteristics of goat farmers in the study area reflected limited resources and knowledge, which contributed to the inadequate adoption of GFP.